HEALING PARK TAMAN MATARAM: REALIZING A SUSTAINABLE JAKARTA CITY THROUGH GREEN INFRASTRUCTURE - Eko Adhy Setiawan; Olivia Seanders (Journal of Synergy Landscape, 2025)
Rapid urbanization in Jakarta has caused an increasing need for green open space (RTH) to solve environmental and social problems. Mataram Park in South Jakarta is a green open space (RTH) that has been converted into a Healing Park to improve the physical and mental well-being of the community, especially in facing the psychosocial impact of the COVID-19 pandemic. This article discusses the application of the Healing Park or Therapeutic Garden concept in Taman Mataram as part of the green infrastructure that supports sustainable development in Jakarta. This research uses a descriptive-analytical approach with field observations and interviews to analyze the park's design and its ecological benefits. The research results show that Mataram Park provides various benefits, such as soil and water conservation, climate change mitigation, and improved air quality. In addition, this park improves people's quality of life by providing space for social interaction, relaxation, and physical activity. Implementing Healing Park has proven effective in reducing stress, improving physical and mental well-being, and providing a space that supports social interaction in urban areas. This research suggests expanding environmentally friendly green spaces and integrating technology in park design to support urban sustainability.